The Bronx is burning: Urban disinvestment effects of the fair access to insurance requirements - Ingrid Gould Ellen; Daniel A. Hartley; Jeffrey Lin; Wei You (Federal Reserve Bank of Chicago, 2024)
In response to private insurers' postwar withdrawal from urban neighborhoods, roughly half of US states developed programs in the late 1960s that offered residual property insurance to property owners denied in the private market. These plans, known as Fair Access to Insurance Requirements (FAIR) plans after 1968, inadvertently encouraged moral hazard through underwriting restrictions, risk pooling, and generous payouts. We use a triple-difference design to estimate FAIR's impact, comparing: (1) pre- and post-FAIR participation periods, (2) neighborhoods likely offered FAIR plans versus those not, and (3) similar contrasts in non-participating states. FAIR plans led to significant housing disinvestment and declines in central neighborhood population and income in the late 1960s and 1970s.
Keywords: G52; N92; R31; 330; Arson; Housing disinvestment; Moral hazard; Neighborhoods; Property insurance